2014
DOI: 10.1242/jeb.105619
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular nutrient absorption is higher in bats than rodents: integrating from intact animals to the molecular level

Abstract: Flying vertebrates have been hypothesized to rely heavily on paracellular absorption of nutrients to compensate for having smaller intestines than non-flyers. We tested this hypothesis in an insectivorous bat (Myotis lucifugus) and two insect-eating rodents (Onychomys leucogaster and Peromyscus leucopus). In intact animals, the fractional absorption of orally dosed L-arabinose (M r 150) was 82% in M. lucifugus, which was more than twice that of the rodents. Absorption of creatinine (M r 113) was greater than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 65 publications
3
27
0
Order By: Relevance
“…For bats, a similar analysis needs to be conducted, but summed nutrient uptakes were not particularly high or low for a single fruit bat species compared with other mammals (44) (FIGURE 5). Furthermore, in intestinal luminal perfusion studies comparing birds or bats with nonflying mammals, we have failed to find differences between taxonomic groups in uptake of glucose or proline per unit length or nominal surface area (12,57,87). Thus the sometimes greater villous amplification ratio discussed above might increase the absorptive surface area, but it does not seem to result in greater mediated absorption in birds and bats.…”
Section: Meeting Absorptive Demand With Smaller Intestines By Greatermentioning
confidence: 81%
See 1 more Smart Citation
“…For bats, a similar analysis needs to be conducted, but summed nutrient uptakes were not particularly high or low for a single fruit bat species compared with other mammals (44) (FIGURE 5). Furthermore, in intestinal luminal perfusion studies comparing birds or bats with nonflying mammals, we have failed to find differences between taxonomic groups in uptake of glucose or proline per unit length or nominal surface area (12,57,87). Thus the sometimes greater villous amplification ratio discussed above might increase the absorptive surface area, but it does not seem to result in greater mediated absorption in birds and bats.…”
Section: Meeting Absorptive Demand With Smaller Intestines By Greatermentioning
confidence: 81%
“…Fractional absorption is measured in intact animals using methods that are standard in pharmacology. Small birds in particular absorb the majority of orally dosed paracellular probes (3, 17-19, 40, 62, 64, 77, 108), whereas absorption of the same probes in small nonflying mammals is much lower (12,28,40,87). This difference declines with increasing body size, such that large birds have similar fractional absorption of paracellular probes as nonflying mammals (16,56).…”
Section: Meeting Absorptive Demand With Smaller Intestines Via Highermentioning
confidence: 99%
“…In our work on sugar absorption, we have used radiolabeled L-glucose (MW=180.6), if possible, or L-arabinose (MW=150.1) and L-rhamnose (MW=164.2) (Caviedes-Vidal et al, 2007;Price et al, 2015). We have validated all of these molecules as probes of passive absorption in birds, bats and non-flying mammals Price et al, 2014). Because these probes do not interact with intestinal transporters, if they are orally administered to intact animals and then appear in blood or urine, this is evidence of paracellular absorption somewhere along the gastrointestinal tract.…”
Section: Controversy About the Contribution Of Glut2mentioning
confidence: 99%
“…An alternative, but not mutually exclusive, mechanistic explanation for higher paracellular absorption is that there are differences in the proteins that makeup the TJs and influence the permeability of each TJ (Price et al, , ). We suspect that there are differences in TJ permeability between bats and rodents, because the ratio of whole‐animal fractional absorption to whole intestine VSA (our proxy of number of tight junctions) in bats still exceeds that of rodents (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…This may make functional sense, because the amino acid products of protein digestion tend to have smaller molecular masses and radii than the monosaccharide products of carbohydrate digestion. Studies in bats and rodents have shown that smaller paracellular probes (such as creatinine, which models the paracellular absorption of amino acids) are absorbed to a much greater extent than larger, glucose‐sized paracellular probes (Dominguez & Pomerene, ; Lundholm & Svedmyr, ; Pappenheimer, ; Price et al, ; Price et al, ; Turner, Cohen, Mrsny, & Madara, ). It is plausible that there has been less natural selection for high SEF and paracellular permeability in carnivores and insectivores compared to herbivores and omnivores.…”
Section: Discussionmentioning
confidence: 99%